2014
DOI: 10.1002/j.2168-0159.2014.tb00246.x
|View full text |Cite
|
Sign up to set email alerts
|

P‐2: High Mobility Zinc Oxynitride TFT for AMOLED

Abstract: Both etch stopped and back channel etched structure TFTs with zinc oxynitride(ZnON) as active layer were developed, and the saturation mobility achieved 33 cm 2 /Vs. The ZnON TFTs show superior positive gate bias stress under dark and light illumination. Furthermore, a 5 inch WOLED panel driven by ZnON TFT was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Owing to the small effective mass of an electron in ZnON (0.19 m e , where m e is the rest mass of an electron), ZnON TFTs exhibit higher mobilities ( μ FE ≃ 30-100 cm 2 V −1 s −1 ) than conventional a-IGZO TFTs. [5][6][7][8][9][10][11][12][13] Over the past few years, various studies have been performed to improve both the electrical performance and stability of ZnON TFTs. [5][6][7][8][9][10][11][12][13][14] Kim et al investigated the effects of Ga doping on the electrical performance of ZnON TFTs, 8) while Ok et al examined the effects of post deposition annealing time on the negative-bias illumination stress stability of ZnON TFTs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the small effective mass of an electron in ZnON (0.19 m e , where m e is the rest mass of an electron), ZnON TFTs exhibit higher mobilities ( μ FE ≃ 30-100 cm 2 V −1 s −1 ) than conventional a-IGZO TFTs. [5][6][7][8][9][10][11][12][13] Over the past few years, various studies have been performed to improve both the electrical performance and stability of ZnON TFTs. [5][6][7][8][9][10][11][12][13][14] Kim et al investigated the effects of Ga doping on the electrical performance of ZnON TFTs, 8) while Ok et al examined the effects of post deposition annealing time on the negative-bias illumination stress stability of ZnON TFTs.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] Over the past few years, various studies have been performed to improve both the electrical performance and stability of ZnON TFTs. [5][6][7][8][9][10][11][12][13][14] Kim et al investigated the effects of Ga doping on the electrical performance of ZnON TFTs, 8) while Ok et al examined the effects of post deposition annealing time on the negative-bias illumination stress stability of ZnON TFTs. 10) In addition, Lee et al successfully fabricated ZnON TFTs with high mobility and reliability by Ar plasma treatment, 11) while Kuan et al demonstrated the excellent electrical characteristics of ZnON TFTs (high μ FE of 71 cm 2 V −1 s −1 ) with a channel length of 0.6 µm.…”
mentioning
confidence: 99%
“…Since the first report by Ye et al [5], zinc oxynitride (ZnON) was considered as a new active material for high-mobility oxide TFTs following an anion control strategy based on the replacement of oxygen by nitrogen in ZnO. Because of the smaller effective mass of an electron in the ZnON (0.19 m e , where m e is the rest mass of an electron) than in the a-IGZO (0.34 m e ) [6,7], ZnON TFTs exhibit higher μ FE s (∼30-100 cm 2 V −1 •s −1 ) than the conventional a-IGZO TFTs [8][9][10][11][12][13][14][15][16]. In addition, the incorporated nitrogen deactivates the oxygen-related defects by raising the valence band above the oxygen-related defect levels, which improves the electrical stability of the device under light illumination [6].…”
mentioning
confidence: 99%
“…During the past several years, various studies have been conducted on ZnON TFTs to improve the electrical performance of the device [8][9][10][11][12][13][14][15][16]. However, the effects of water absorption on the electrical performance and stability of the ZnON TFTs were not investigated, even though the ambient humidity significantly affects the electrical performance and stability of the oxide semiconductor TFTs [17][18][19][20].…”
mentioning
confidence: 99%
“…attracting significant attention as potential alternatives to amorphous indium-gallium-zinc oxide (IGZO) TFTs in next-generation largesized high-resolution displays owing to their high field-effect mobility (μ FE = ∼ 40-120 cm 2 /V•s) and excellent photostability. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] ZnON is an alloy of an oxide (ZnO) and a nitride (Zn 3 N 2 ) having the same Zn cation. Because of the lower electron effective mass in ZnON (0.19 m e , where m e is the rest mass of an electron) than in IGZO (0.34 m e ), 3 ZnON TFTs have a higher μ FE compared to conventional IGZO TFTs (μ FE = ∼10-20 cm 2 /V•s).…”
mentioning
confidence: 99%